Pin1 Binding to Phosphorylated PSD-95 Regulates the Number of Functional Excitatory Synapses - Delgado, Jary Y.; Nall, Duncan; Selvin, Paul R. (Frontiers in Molecular Neuroscience, 2020)
The postsynaptic density protein 95 (PSD-95) plays a central role in excitatory synapse development and synaptic plasticity. Phosphorylation of the N-terminus of PSD-95 at threonine 19 (T19) and serine 25 (S25) decreases PSD-95 stability at synapses; however, a molecular mechanism linking PSD-95 phosphorylation to altered synaptic stability is lacking. Here, we show that phosphorylation of T19/S25 recruits the phosphorylation-dependent peptidyl-prolyl cis-trans isomerase (Pin1) and reduces the palmitoylation of Cysteine 3 and Cysteine 5 in PSD-95. This reduction in PSD-95 palmitoylation accounts for the observed loss in the number of dendritic PSD-95 clusters, the increased AMPAR mobility, and the decreased number of functional excitatory synapses. We find the effects of Pin1 overexpression were all rescued by manipulations aimed at increasing the levels of PSD-95 palmitoylation. Therefore, Pin1 is a key signaling molecule that regulates the stability of excitatory synapses and may participate in the destabilization of PSD-95 following the induction of synaptic plasticity.